Optimisation of ECM parameters using RSM and non-dominated sorting genetic algorithm (NSGA II). (1st January 2013) - Senthilkumar, C.; Ganesan, G.; Karthikeyan, R.
Metal matrix composites (MMC) are hard to machine due to the presence of hard and brittle ceramic reinforcements. Electro chemical machining (ECM) is an important process for machining such materials. Being a complex process, it is very difficult to determine optimal parameters for improving cutting performance. The objective of this research is to study the effect of electrolyte flow rate, applied voltage, electrolyte concentration, and tool feed rate on metal removal rate (MRR) and surface roughness (Ra). In the present work, response surface methodology (RSM) and a multi-objective optimisation method based on a non-dominated sorting genetic algorithm (NSGA-II) is used to optimise ECM process. A non-dominated solution set has been obtained and reported.